2005
DOI: 10.1152/japplphysiol.01290.2004
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function of young healthy males following whole body resistance training

Abstract: Given the increasing emphasis on performance of resistance exercise as an essential component of health, we evaluated, using a prospective longitudinal design, the potential for resistance training to affect arterial endothelial function. Twenty-eight men (23 +/- 3.9 yr old; mean +/- SE) engaged in 12 wk of whole body resistance training five times per week using a repeating split-body 3-day cycle. Brachial endothelial function was measured using occlusion cuff-induced flow-mediated dilation. After occlusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 32 publications
5
117
1
7
Order By: Relevance
“…Recent studies reported that resistance training or aerobic training increased brachial and femoral artery diameter. 31,[34][35][36] These results suggest that both types of training cause enlargement at the level of the major conduit arteries. The present findings extend these results from endurance-trained individuals to those who perform resistance training.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 69%
See 1 more Smart Citation
“…Recent studies reported that resistance training or aerobic training increased brachial and femoral artery diameter. 31,[34][35][36] These results suggest that both types of training cause enlargement at the level of the major conduit arteries. The present findings extend these results from endurance-trained individuals to those who perform resistance training.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 69%
“…These results are consistent with those of a previous study. 31 However, the previous study increased the training load stepwise during the training period. As this study involved a high-intensity training load from the start, our findings are important.…”
Section: Muscle Contraction Timing and Vascular Function T Okamoto Et Almentioning
confidence: 96%
“…10,11,19 In agreement with our findings, Collier et al 11 demonstrated that 4 weeks of RET increased resting FBF in middle-aged men and women with pre-hypertension. Furthermore, previous studies demonstrated that 6 10 and 12 36 weeks of RET increased FBF and vasodilatory capacity at rest in young men. Moreover, Olson et al 9 found an increase in resting brachial flowmediated dilation after 1 year of moderate-intensity RET in overweight premenopausal women.…”
Section: Discussionmentioning
confidence: 80%
“…11,12 However, these findings are controversial, as not all studies show an increase in arterial stiffness with resistance training. 13,14 Increases in arterial stiffness, which are associated with increased mortality and morbidity, can lead to decreases in blood flow because of increased peripheral resistance. 15 As arterial stiffness is related to increased pulse pressure and myocardial load, RE may potentially lead to myocardial hypertrophy.…”
Section: Introductionmentioning
confidence: 99%